"User perception on Library Counter Service Staff" - A case study at Penampang State Library / Laikim Ginsalu - Ginsalu, Laikim (2009)
This paper seek to examine the perception on the role of"The User Perception on Counter Service Staff" A study in Sabah State Library in Penampang Branch.